Analisis Yuridis Manajemen Risiko dalam Pelaksanaan Bancassurance di Indonesia Berdasarkan Surat Edaran Otoritas Jasa Keuangan Nomor 33/SEOJK.03/2016 tentang Penerapan Manajemen Risiko pada Bancassurance - Widhianti, Kris; Reykasari, Yunita (Journal of Contemporary Law Studies, 2023)
The concept of bancassurance is that banks act as intermediaries in helping insurance companies reach their target customers with the aim of increasing market share. Financial Services Authority supervision of bancas-surance needs to be carried out. In reality, the implementation of bancassurance does not necessarily always comply with the Financial Services Authority Circular Letter Number 33/SEOJK.03/2016 and allows for future risks. The implementation of bancassurance allows for operational, legal and reputation risks. Risk management is carried out to avoid the possibility of these risks occurring. Therefore, the question arises about the role of the Financial Services Authority in mitigating the implementation of bancassurance in Indonesia. This research uses a statutory and conceptual approach with a normative juridical research type. The initial mitigation in implementing bancassurance is by selecting the right insurance company partner in accordance with the advantages and benefits for carrying out cooperation to the work plan and approval from the financial services authority as the supervisory institution. Banks are required to have written procedures to manage the risks inherent in bancassurance activities which include systems and procedures as well as authority; identification of all inherent risks; risk measurement and monitoring methods; accounting recording methods; analysis of legal aspects; and transparency of information to customers.